2020
DOI: 10.1007/s10295-020-02323-2
|View full text |Cite
|
Sign up to set email alerts
|

Production of d-Glyceric acid from d-Galacturonate in Escherichia coli

Abstract: A microbial production platform has been developed in Escherichia coli to synthesize d-glyceric acid from d-galacturonate. The expression of uronate dehydrogenase (udh) from Pseudomonas syringae and galactarolactone isomerase (gli) from Agrobacterium fabrum, along with the inactivation of garK, encoding for glycerate kinase, enables d-glyceric acid accumulation by utilizing the endogenous expression of galactarate dehydratase (garD), 5-keto-4-deoxy-D-glucarate aldolase (garL), and 2-hydroxy-3-oxopropionate red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…To characterize this system, we conducted fermentations with the MG1655(DE3) ΔgarK Δhyi ΔglxK ΔuxaC strain used previously. [30] We verified that the control circuit modulates transcription in response to galacturonate by quantifying the relative mRNA levels of udh, the second gene in the operon, over the course of a fermentation using qRT-PCR (Figure 5A). For all samples, the fold change of mRNA was analyzed relative to P1OO levels before galaturonate addition.…”
Section: Feed Activated Expression Of a D-glyceric Acid Production Pa...mentioning
confidence: 83%
See 3 more Smart Citations
“…To characterize this system, we conducted fermentations with the MG1655(DE3) ΔgarK Δhyi ΔglxK ΔuxaC strain used previously. [30] We verified that the control circuit modulates transcription in response to galacturonate by quantifying the relative mRNA levels of udh, the second gene in the operon, over the course of a fermentation using qRT-PCR (Figure 5A). For all samples, the fold change of mRNA was analyzed relative to P1OO levels before galaturonate addition.…”
Section: Feed Activated Expression Of a D-glyceric Acid Production Pa...mentioning
confidence: 83%
“…The biosensor controlled pathway and constitutive pathway plasmids (pP1OO-gli-udh and pP1XX-gliudh in SI Table S4, respectively) were constructed with the PCR products of P1OO-f and P1OO-r on template pP1OO-gfp or P1XX-gfp, and gli-f and gli-r, plus udh-f and udh-r on the previously constructed pathway plasmid, [30] using NEBuilder HiFi DNA Assembly Cloning Kit (NEB). RBS sequences for the operon (SI Table S3), calculated using the Operon Calculator function of the RBS Calculator, [42] were included in the primers (SI Table S2).…”
Section: Cloning and Plasmid Constructionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that CBLEB alleviates the faecal enrichment of 1-octadecanol, 2-propenoic acid, 2.4-di-tert-butylphenol, D-lyxose, glyceric acid and m-cresol, as well as the depletion of (Z,Z)-9,12-octadecadienoic acid in immunocompromised SP-infection rats. Among these metabolites, 1-octadecanol, glyceric acid and (Z,Z)-9,12-octadecadienoic acid are commonly found in animals, plants and microbes and can also be used in cosmetics, medicines or food additives; [30][31][32] D-lyxose, a rare pentose found in bacterial glycolipids, is not usually utilized by microbes and is a precursor to antitumour and immunostimulatory α-galactosylceramide agents; 33 and 2-propenoic acid, 2.4-di-tert-butylphenol and m-cresol are compounds with low toxicity and antioxidant functions. [34][35][36] Nevertheless, the effects of these compounds on the lung and gut are not fully understood.…”
mentioning
confidence: 99%